2020
DOI: 10.1038/s41598-020-74481-3
|View full text |Cite
|
Sign up to set email alerts
|

Repeated stress exposure in mid-adolescence attenuates behavioral, noradrenergic, and epigenetic effects of trauma-like stress in early adult male rats

Abstract: Stress in adolescence can regulate vulnerability to traumatic stress in adulthood through region-specific epigenetic activity and catecholamine levels. We hypothesized that stress in adolescence would increase adult trauma vulnerability by impairing extinction-retention, a deficit in PTSD, by (1) altering class IIa histone deacetylases (HDACs), which integrate effects of stress on gene expression, and (2) enhancing norepinephrine in brain regions regulating cognitive effects of trauma. We investigated the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 113 publications
0
15
0
Order By: Relevance
“…Timing combined with stressor modality seem to be an important factor as well. In this sense, prior work indicates adult resilience even after a single intense stressor protocol at PND37 or following 3 days of predator related stressors at PND33-35 (46). In contrast, a 3-day pre-pubertal exposure to variate stressors failed to attenuate exaggeration of fear responses in adulthood, indicating that developmental timing is critical for establishment of resilience.…”
Section: Discussionmentioning
confidence: 95%
“…Timing combined with stressor modality seem to be an important factor as well. In this sense, prior work indicates adult resilience even after a single intense stressor protocol at PND37 or following 3 days of predator related stressors at PND33-35 (46). In contrast, a 3-day pre-pubertal exposure to variate stressors failed to attenuate exaggeration of fear responses in adulthood, indicating that developmental timing is critical for establishment of resilience.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, we focused on the main brain regions of the reward pathway (PFC, anterior STR, NAc) as well as the two primary brain structures of the limbic system (HC and AMYG) as traumatic stress and chronic alcohol exposure are known to disrupt the function of those circuits [ 17 , 18 , 19 , 59 , 60 , 61 ], and brain regions within those pathways contain abundant levels of CB system components [ 17 , 22 , 23 , 24 ]. The PFC is one of the main reward-associated brain regions, and it plays an important role in working memory, executive function, emotional and motivational regulation, learning extinction, and decision-making [ 9 , 11 , 12 , 13 , 21 , 62 , 63 , 64 ]. Animal studies have shown that repeated restraint stress in both mice and rats decreases AEA content but increases 2-AG content in the medial PFC [ 47 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The STR is another main reward-associated brain region that plays an important role in regulating motivation, habitual action and learning, goal-directed behaviors, and cognition, and studies have shown that alcohol exposure alters striatal function [ 11 , 12 , 20 , 64 , 69 , 70 , 71 , 72 , 73 , 74 ]. Our results showed that both AEA and 2-AG content increased in the anterior STR after mice were exposed to both mSPS and CIE compared to mice exposed to mSPS only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations